Hydrolase–like catalysis and structural resolution of natural products by a metal–organic framework - Marta Mon (Nature Portfolio, 2020)
Elucidation of the chemical structure of natural products constitutes one of the main challenges in Natural Sciences. Here, the authors show that an amino acid-based metal–organic framework exhibits hydrolase-like catalytic activity and crystallographic determination of the resulting products.